Antibiotic Resistance Pattern of Extended Spectrum Beta Lactamase Producing Escherichia coli Isolated From Patients With Urinary Tract Infection in Morocco - Kettani Halabi, Mohamed; Lahlou, Fatima Azzahra; Diawara, Idrissa; El Adouzi, Younes; Marnaoui, Rabiaa; Benmessaoud, Rachid; Smyej, Imane (Frontiers in Cellular and Infection Microbiology, 2021)
Extended-spectrum β-lactamases producing Escherichia coli (ESBL-EC) lend resistance to most β-lactam antibiotics. Because of limited treatment options, ESBL-EC infections are generally more difficult to treat, leading to higher hospital costs, reduced rates of microbiological and clinical responses, and a threat to the patient’s life. This study aimed to determine the antibiotic resistance pattern of ESBL-EC isolated from patients with urinary tract infection in Morocco. This retrospective laboratory-based study was conducted at Cheikh Khalifa International University Hospital, Casablanca, from January 2016 to June 2019. A total of 670 urine samples were collected from urinary tract infection patients and processed by standard microbiological methods. In vitro susceptibility testing to different antibiotics of all identified isolates of Escherichia coli (E. coli) was performed following Kirby–Bauer’s disc diffusion method on Mueller–Hinton Agar according to the EUCAST standards. The reviewing of ESBL-EC was confirmed by the appearance of a characteristically shaped zone referred to as a “champagne cork” using the Combined Disk Test. Among a total of 438 E. coli isolated from nonrepetitive urine samples, two hundred fifty-nine (59%) were ESBL-EC, of which 200 (77%) were isolated from adult patients (over the age of 50) and the majority were female. All ESBL-EC isolates were resistant to third-generation cephalosporin and quinolones and sensitive to carbapenem and fosfomycin. Knowledge of antimicrobial resistance patterns in ESBL-EC, the major pathogen associated with urinary tract infection, is indispensable as a guide in choosing empirical antimicrobial treatment.